2012
DOI: 10.1111/j.1365-2427.2012.02792.x
|View full text |Cite
|
Sign up to set email alerts
|

Appearance and establishment of diazotrophic cyanobacteria in Lake Kinneret, Israel

Abstract: Summary 1. We propose that the appearance and establishment of Nostocales (cyanobacteria) species of the genera Aphanizomenon and Cylindrospermopsis in the warm subtropical Lake Kinneret (Sea of Galilee, Israel) from 1994 was linked to changes in climate conditions and summer nitrogen (N) availability. 2. From 1994 to 2009, an increase in frequency of events of elevated water temperature (>29 °C) in summer, and to some extent a greater frequency of lower summer wind speed events, affected water turbulence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 55 publications
(97 reference statements)
1
25
0
Order By: Relevance
“…The reason that Nostocales species appear to be dominating the invasion into freshwater oligotrophic lakes as reported in the literature (Hadas et al ., ; Sinha et al ., ; Sukenik et al ., ) may result from the fact that these bacteria are more skilled to cope with increasing CO 2 availability and increased intracellular carbon levels by increasing their nitrogen levels through in‐house dinitrogen fixation. Non‐nitrogen‐fixing organisms would be unable to obtain enough inorganic nitrogen from internal nitrogen cycling within the sediment to maintain a dense, toxin or nontoxin‐producing bloom (Sukenik et al ., ).…”
Section: Hepatotoxin Production Under Changing Climatic Conditions Anmentioning
confidence: 99%
“…The reason that Nostocales species appear to be dominating the invasion into freshwater oligotrophic lakes as reported in the literature (Hadas et al ., ; Sinha et al ., ; Sukenik et al ., ) may result from the fact that these bacteria are more skilled to cope with increasing CO 2 availability and increased intracellular carbon levels by increasing their nitrogen levels through in‐house dinitrogen fixation. Non‐nitrogen‐fixing organisms would be unable to obtain enough inorganic nitrogen from internal nitrogen cycling within the sediment to maintain a dense, toxin or nontoxin‐producing bloom (Sukenik et al ., ).…”
Section: Hepatotoxin Production Under Changing Climatic Conditions Anmentioning
confidence: 99%
“…Since the main source of P in Lake Kinneret during the summer is through the exchange with sediments, it is not clear what caused the large difference between two consecutive years with respect to P availability. In an earlier study we raised the possibility that the invasion of the diazotrophic Nostocals Aphanizomenon and C. raciborskii to Lake Kinneret since 1994 may be attributed to local meteorological changes (Hadas et al ., 2012). We compared specific abiotic and biological parameters to examine whether they could contribute to the marked differences between the Aphanizomenon populations and gene expressions therein in the springs of 2009 and 2010 (Figs 4 and 5).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies (Hadas et al ., 2012; Sukenik et al ., 2012) suggested that the invasion of filamentous cyanobacteria such as Aphanizomenon and Cylindrospermopsis raciborskii to Lake Kinneret was supported by changes in regional meteorological conditions. An earlier study (Hadas et al ., 2002) showed that the abiotic parameters in Lake Kinneret during the first massive Aphanizomenon bloom in 1994 closely matched the optimal conditions for its growth under controlled laboratory conditions and could explain its development during that year.…”
Section: Introductionmentioning
confidence: 99%
“…Slim et al [ 29 ] revealed that changes in climate regime, increase in air temperature and decrease in precipitation between 2000 and 2010 have altered Karaoun Reservoir biodiversity and resulted in low diversity dominated by Chrysosporum ovalisporum and Microcystis aeruginosa blooms. In Lake Kinneret, Hadas et al [ 37 ] proposed that the appearance and establishment of Chrysosporum ovalisporum since 1994 was linked to increased water temperature and limited nitrogen availability. Using a temperature based model, Mehnert et al [ 16 ] hypothesized a future northward expansion of Chrysosporum ovalisporum in Europe under the global warming scenario.…”
Section: Discussionmentioning
confidence: 99%